2022
DOI: 10.3389/fmed.2022.886996
|View full text |Cite
|
Sign up to set email alerts
|

Berberine as a Potential Agent for the Treatment of Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed and deadly malignancies worldwide. The incidence of CRC has been increasing, especially in young people. Although great advances have been made in managing CRC, the prognosis is unfavorable. Numerous studies have shown that berberine (BBR) is a safe and effective agent presenting significant antitumor effects. Nevertheless, the detailed underlying mechanism in treating CRC remains indistinct. In this review, we herein offer beneficial evidence for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 202 publications
(201 reference statements)
0
16
0
Order By: Relevance
“…Studies in the literature have also shown that berberine is used in humans. Jiang et al reported that berberine is a safe and effective drug in patients with colorectal cancer and is beneficial in the treatment of these patients 20 . Similarly, human studies have shown that berberine is an effective agent in neurodegenerative disorders such as the Parkinson’s and Alzheimer’s diseases due to its potent antioxidant effect 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature have also shown that berberine is used in humans. Jiang et al reported that berberine is a safe and effective drug in patients with colorectal cancer and is beneficial in the treatment of these patients 20 . Similarly, human studies have shown that berberine is an effective agent in neurodegenerative disorders such as the Parkinson’s and Alzheimer’s diseases due to its potent antioxidant effect 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Coptis chinensis and Coptis teeta have been medicinally used in Eastern Asian regions for treating symptoms related to “damp-heat” of the body, such as fever, swelling, or dyspepsia. Berberine, a monomeric alkaloid compound included in Coptis, has been studied in previous studies and proven to exert anti-cancer effects by multiple mechanisms [ 141 , 142 , 143 , 144 , 145 ]. A recent study showed that berberine could alleviate CIPN symptoms induced by cisplatin treatment [ 74 ] as well.…”
Section: Candidates For New Therapeutics: Approach With Knowledge Fro...mentioning
confidence: 99%
“…The colorectal cancer is the third most common cancer in the world, accounting for more than a third of all cancer cases worldwide, and the mortality rate is usually high (1,2).…”
Section: Introductionmentioning
confidence: 99%